PERTANGGUNGJAWABAN PIDANA PENGURUS KOPERASI JASA DALAM TINDAK PIDANA PEMERASAN - Esron Silaban; Alvi Syahrin; Edy Yunara; Muhammad Ekaputra (Universitas Sumatera Utara, 2018)
ABSTRACT Cooperative was founded on the principle of kinship and berasaskan helping to carry out remedial level economic life of mole-people who belong to a group of workers or those who fall into poverty as a result of the implementation of the system of capitalism. However, the cooperative in carrying out its business is inseparable from the possibility of a criminal act, one of which is extortion punishment committed by the cooperative management of the loading and unloading of labor services at the port, which extortion is carried out by the cooperative management on behalf of the cooperative and the proceeds of the crime are accommodated Governed entirely by cooperatives for the benefit of cooperative members. Based on the background then in the formulation of the problem that is: 1) How is the criminal accountability of the cooperative management over the criminal acts of extortion against third parties 2) Can the cooperative be held accountable for money laundering crimes derived from extortion crimes committed by cooperative management? Can the cooperative be held accountable for money laundering crimes derived from extortion crimes committed by cooperative management? The purpose of this study to determine and analyze the criminal responsibility of the cooperative management of the crime of extortion against third parties and to identify and analyze whether the cooperative could be held accountable for laundering money derived from criminal acts of extortion by the cooperative board. Keywords: Management, Cooperatives, Criminal Accountability, Extortion, Money laundering